(untitled) (SCIENCE TIME JOURNAL, 2026)
The growing presence of artificial intelligence (AI) in higher education has begun to influence how English as a Foreign Language (EFL) is taught and learned at the university level. AI-driven tools such as automated writing feedback systems, speech recognition software, and conversational agents are increasingly used to supplement traditional instruction. This article examines the pedagogical role of artificial intelligence in university EFL classrooms, with particular attention to its impact on language development, learner autonomy, and instructional practices. Drawing on classroom-based implementation, learner performance data, and student and teacher perspectives, the study suggests that AI can enhance personalized learning and provide timely feedback, especially in writing and speaking. At the same time, the findings highlight the importance of teacher mediation and ethical awareness in AI integration. The article concludes by arguing that AI is most effective when used as a supportive pedagogical tool rather than a replacement for human instruction.